Electrochemical Behavior of TiO2 Nanoparticle Doped WO3 Thin Films. (6th May 2014) - Bathe, Suvarna R.; Patil, P. S.
Abstract : Nanoparticle TiO2 doped WO3 thin films by pulsed spray pyrolysis technique have been studied on fluorine tin doped (FTO) and glass substrate. XRD shows amorphous nature for undoped and anatase phase of TiO2 having (101) plane for nanoparticle TiO2 doped WO3 thin film. SEM shows microfibrous reticulated porous network for WO3 with 600 nm fiber diameter and nanocrystalline having size 40 nm for TiO2 nanoparticle doped WO3 thin film. TiO2 nanoparticle doped WO3 thin film shows 95% reversibility due to may be attributed to nanocrystalline nature of the film, which helpful for charge insertion and deinsertion process. The diffusion coefficient for TiO2 nanoparticle doped WO3 film is less than undoped WO3 .